Порівняльне вивчення фітохімічного складу бруньок нетрадиційних плодових рослин - Dzurenko, N.I.; Palamarchuk, O.P.; Koval, I.V.; Skrypchenko, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2014)
The paper presents the results of the comparative estimation of buds of non-traditional fruit plants as a natural source of biologically active substances. The buds of these plants accumulate significant amount of flavonoid compounds with P-vitamin activity, tannins, vitamin C, chlorophyll, carotenoids, the quantity of which is changed according to species and the phase of it growth. On the base of obtained results the buds of some species of non-traditional fruit plants may be consided as perspective source of biologically active substances with P-vitamin activity (sea buckthorn) and polysaccharides (actinidia, grape, sea buckthorn, schizandra, viburnum).